The relevancy of sex education in secondary schools / Muhammad Firdaus Azmi, Izwandy Abu Bakar and Syed Ismail Wan Drahman - Azmi, Muhammad Firdaus; Abu Bakar, Izwandy; Wan Drahman, Syed Ismail (2011)
Sex education is a form of education that gives the students information about healthy sexual relationship, forming attitudes and beliefs about sex, sexual identity, relationship and sexual intimacy. It is also educations that develop young people skills on how they think about sex itself and it is can be consider as one way to help them make the right choices in their life. In Malaysia sex education has been implemented in secondary schools. But in the form of other subject such as biology, science and so on. The current news that the government may implement sex education as a subject in secondary schools received a lot of attentions from the educators themselves, the parents, students, Ministry of Education, researchers and people that involve directly and indirectly in this matter. These people give both negative and positive respond toward that plan to implement sex education. We do believe that it is time to get the opinion from the party that get the most effect from the implementation of this matter; the students, parents and also the teachers. It is because any action taken by the government will somehow affect these three parties. by knowing their point of views and considering the other factors as well, we believe that this project can help to solve the issue whether the implementation of sex education in secondary school is relevant or not.